(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: public health requires strong information skills and competencies, as it is information-intensive and information-driven. Public health informatics has been defined as the “systematic application of information, computer science, and technology to public health practice, research, and learning”. New information and communication technologies offer unprecedented opportunities, such as linking smart-phones and mobiles devices to web based tools for data collection, enabling and enhancing participatory epidemiology. However, being an emerging discipline, despite its potential and importance, public health informatics is often neglected and overlooked, being rarely offered as course. The present study was designed as a pilot study, with the aim of designing and validating a questionnaire on the knowledge of public health informatics among medical residents in public health in Italy. Methods and Results: thirty-two Italian residents in public health volunteered to take part into the study. Mean age of the sample was 31.44±2.23 years, most responders were males (68.8%), from northern Italy (53.1%), at the third year of residency (34.4%) and currently doing practical training at the clinical management staff/hospital directorate (34.4%). Other places of training were the Prevention Department (21.9%), the Institute of Hygiene (18.8%), the local health units and the territory (12.5%), the occupational health service (6.3%) and the Regional Health Agency (3.1%). Cronbach’s alpha coefficient yielded a value of 0.909, demonstrating excellent psychometric properties of the instrument. Conclusion: in conclusion, the developed questionnaire seems to be an appropriate and useful tool to detect gaps concerning knowledge, education and practices of public health informatics among residents in public health.